2010
DOI: 10.1021/jp9121563
|View full text |Cite
|
Sign up to set email alerts
|

Change of Structural Behaviors of Organo-Silane Exposed Graphene Nanoflakes

Abstract: The electronic structures of graphene nanoflakes (GNFs) exposed to an organo-silane precursor [tetramethylsilane, TMS, Si(CH 3) 4 ] were studied using electron field emission (EFE), Raman spectroscopy, X-ray absorption near-edge structure (XANES), X-ray photoelectron spectroscopy (XPS), X-ray emission spectroscopy (XES), and first-principles calculation. The results of XANES, XPS, and Raman spectroscopy indicate that the silyl radical strong covalent bonds were formed in GNFs, which induced local structural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The features C 1 and C 5 at approximately 285.5 and 292 eV in the C K -edge XANES spectra of HOPG are attributed to the C 1 s → π* and 1 s → σ* transitions, respectively. The π*-feature ( C 1 ) is typical of the out-of plane C = C or graphitic sp 2 bond, while the in-plane σ*-feature ( C 5 ) is typical of the C-C bond 25 28 . In contrast, a similar line-shape and position of the HOPG can be seen relative to those of the σ*-feature ( C 5 ) in the GO and rGOs, whereas the π*-feature (C 1 ) is shifted 0.4 eV below and 0.1 eV above the GO and rGOs, respectively, relative to that of HOPG, as indicated by the dashed line in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The features C 1 and C 5 at approximately 285.5 and 292 eV in the C K -edge XANES spectra of HOPG are attributed to the C 1 s → π* and 1 s → σ* transitions, respectively. The π*-feature ( C 1 ) is typical of the out-of plane C = C or graphitic sp 2 bond, while the in-plane σ*-feature ( C 5 ) is typical of the C-C bond 25 28 . In contrast, a similar line-shape and position of the HOPG can be seen relative to those of the σ*-feature ( C 5 ) in the GO and rGOs, whereas the π*-feature (C 1 ) is shifted 0.4 eV below and 0.1 eV above the GO and rGOs, respectively, relative to that of HOPG, as indicated by the dashed line in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…While, Ray et al have observed a similar feature in the 287-291 eV range for amorphous a-C:H(OH) thin films and attributed it to a combination of the C-H * bonding with the O-C=C, C-OH and C=O * bonds. 35,41 Pacile et al have attributed it to the splitting of the * bands in graphene and to interlayer state related to the charge density between graphene layers. 43 Nevertheless, for the FLG:N(PECVD) samples, the increase in the feature at ~288 eV can be attributed to the increase in the C-H intensity which indicates the formation of sp 3 -rich structures having a higher content of C-H bonds, thus confirming the Raman and EFE analysis of the previous section.…”
Section: 39mentioning
confidence: 99%
“…9 It was observed by theoretical studies that the substitutionally doped Si atoms in CNTs and/or graphene were found to relax outwards and form sp 3 bonding. [10][11][12] Besides the single Si-impurity in monolayer graphene, Si doped bilayer/multi-layer graphene or graphene nano-ribbons/nano-flakes has been investigated, which shows that there is a covalent bonding of Si-atoms between different layers. 12,13 However, there are few experimental studies reported on Si-doped graphene and/or graphene nano-ribbons/nano-flakes, therefore it is important to give new insights into the electronic structure, chemical bonding, and their possible applications.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Besides the single Si-impurity in monolayer graphene, Si doped bilayer/multi-layer graphene or graphene nano-ribbons/nano-flakes has been investigated, which shows that there is a covalent bonding of Si-atoms between different layers. 12,13 However, there are few experimental studies reported on Si-doped graphene and/or graphene nano-ribbons/nano-flakes, therefore it is important to give new insights into the electronic structure, chemical bonding, and their possible applications. Graphene nano flakes (GNFs), the derived graphene materials are quasi-two-dimensional networks of vertically aligned graphene sheets and have morphologies similar to those of nano carbon materials, such as carbon nanoflakes and nanosheets.…”
Section: Introductionmentioning
confidence: 99%